2012
DOI: 10.1002/vnl.20317
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the addition of nano‐CaCo3 at dry mixing or onset of fusion on the dispersion, torque, and mechanical properties of compounded PVC

Abstract: A Brabender torque rheometer equipped with an internal mixer was used to study the influence of compounding method on the properties of (rigid PVC)/(treated and untreated nano‐CaCO3) nanocomposites. Two different methods were studied for the addition of surface treated and untreated nano‐CaCO3 during the melt mixing of rigid PVC. Direct dry mixing of rigid PVC and nano‐CaCO3, and addition of nano‐CaCO3 at the onset of PVC fusion were investigated. Dispersion of treated and untreated nano‐CaCO3 was studied by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…A similar phenomenon of shortening the time of gelation of PVC modified with CaCO 3 nanoparticles or nanoclay is described in works . When investigating PVC/ASA/MWCNT composites, with the increase in MWCNT fraction in the range from 0.02 to 0.07%, a similar time shortening was also found, which the Authors explain by effect of MWCNT on accelerating of plasticization.…”
Section: Discussion Of the Resultssupporting
confidence: 75%
“…A similar phenomenon of shortening the time of gelation of PVC modified with CaCO 3 nanoparticles or nanoclay is described in works . When investigating PVC/ASA/MWCNT composites, with the increase in MWCNT fraction in the range from 0.02 to 0.07%, a similar time shortening was also found, which the Authors explain by effect of MWCNT on accelerating of plasticization.…”
Section: Discussion Of the Resultssupporting
confidence: 75%
“…The effect of nano-CaCO 3 on the mechanical properties of PVC has been studied by several authors 1,4,5,6 . In the studies of Jazi et al (2012) 7 it was reported that the impact resistance and Young´s modulus were visibly improved with the addition of 5-25 phr (parts by weight per hundred parts of resin) of nano-CaCO 3 , but its elongation at break was reduced. The ideal content of nano-CaCO 3 particles to improve impact resistance was about 15 phr to PVC composites / nano-CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A typical torque curve for flexible grade PVC is shown in Figure 4 Besides giving information about the dynamic thermal stability of a PVC compound, the torque curve also gives information on the viscosity and general flow behaviour of the PVC. The combination of all this information makes the torque rheometer an excellent instrument for gaining insight into the processing behaviour of PVC compounds [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%